PENGEMBANGAN KETERAMPILAN ABAD 21 DALAM PEMBELAJARAN ASAM BASA MELALUI PROYEK STEAM - Achmad Ridwan; Chintia Fatimah; Tritiyatma Hadinugrahaningsih; Yuli Rahmawati; Alin Mardiah (Jurnal Tadris Kimiya, 2022)
This study is aimed to develop students' 21st century skills by integrating STEAM projects (Science, Technology, Engineering, Art, and Mathematics) in learning chemistry on acid and base solutions. Interdisciplinary learning was designed to allow students to be actively involved in learning through project development activities to see the relevance of learning content and its application in real life. This study involved 35 students of natural science 11th grade, consisting of 14 boys and 21 girls, in one of public senior high schools in DKI Jakarta Province. Researchers used qualitative methods to understand students' experiences and the implications of learning on their 21st century skills. The researcher collected data through semi-structured interviews, observation, journal reflective, and 21st century skills questionnaires. The results showed that each stage of STEAM learning integrated with project-based learning encouraged students to develop 21st century skills, namely learning and innovation skills, skills using information, media, technology, and life and career skills. Students reflected their abilities in using information and technology, the ability to work together, communication, and thinking at higher levels, as well as adaptability and leadership. In addition, Students were also faced with challenges in changing the paradigm of teachers and students and managing the learning process.